A new model for reduction of Azimuth asymmetry biases of tropospheric delay. Issue 1 (2nd January 2019) - Nabil, A.; Abdelfatah, M. A.; Mousa, A. E.; El-Fiky, G. S.
ABSTRACT: Nowadays, a GNSS application is one of the main backbones of lifestyle. The GNSS signal that comes from space satellites to receivers on Earth suffers some delays. The troposphere layer is one of the basic sources of delay to signals. To detect the delay, many models have been produced taking into account the receiver location and satellite zenith angle. Most of these models give vertically perfect representation without accounting the horizontal asymmetry effect. The horizontally graded difference "azimuth asymmetry" is negligible at high elevation angles up to 10°. At low elevation angles, the asymmetry is significant. At 2° elevation angle, the asymmetry is about 72 mm for east and west and about 66 mm for south. Using the Precise Tropospheric Delay Database (PTD), the difference in horizontal plane delays is studied. A new model is proposed and compared to PTD calculations. The model has three coefficients obtained for high zenith angles (70° to 88°). These coefficients are modelled as a function of zenith angle and used to give a horizontal gradient factor which is multiplied by the northern mapping function to map it to any azimuth. The proposed model makes significant improvement. For east and west directions, the model decreases the bias from around 72 mm to be about 1.0 mm. For the southern direction, the produced model needs an improvement to get closer to the true asymmetry. Abbreviations : GNSS: Global Navigation Satellite Systems; HG: Horizontal Gradient; MF: Mapping Function; PTD: Precise Tropospheric Delay Database; Z: Zenith Angle; ZHD: Zenith Hydrostatic Delay; ZTD: Zenith Total Delay; ZWD: Zenith Wet Delay